Pengabdian Kepada Masyarakat Melalui Program “Sekolah Bina Cerah” Pada SDN Sumurmati I - Anggara Putra Bimantara; Yanda Bara Kusuma (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
Based on the results of a survey conducted by KKN-T MBKM Group 62 students, there were only 10 MSME actors in Sumurmati Village. With the "Sekolah Bina Cerah" program, the aim is to try to instill and develop entrepreneurial spirit in students at SDN Sumurmati I by providing knowledge to students at SDN Sumurmati I in the form of providing material on entrepreneurship, training in managing finances by saving, and providing skills training in making crafts that have selling points. The implementation of the "Sekolah Bina Cerah" program which was carried out at Sumurmati 1 Elementary School was carried out on the 11th, 17th and 25th of May 2023 which targeted students in grades 4 and 6. From this activity an output was obtained where students could understand what entrepreneurship is, how to manage the money they earn to make it even more useful, and practice directly how to make a craft that has a sale value.